Utilizing a Film Holder to Enhance Radiographic Imaging in Maxillary Molar Trifurcation - Savitri, Yunita; Wahjuni, Otty Ratna; Bosawer, Ellyonord Diana; Astuti, Eha Renwi; Mulyani, Sri Wigati Mardi; Saputra, Deny; Putra, Ramadhan Hardani; Asymal, Alhidayati; Nurrachman, Aga Satria; Ramadhani, Nastiti Faradilla; Lashari, Dur Muhammad (Indonesian Journal of Dental Medicine, 2023)
Background: The parallel technique stands as a prominent method for radiographic examinations aiming to identify furcation involvement. Nevertheless, an inherent limitation lies in the frequent superimposition of the trifurcation region with tooth roots, potentially leading to inaccurate diagnoses. The Same Lingual Opposite Buccal (SLOB) technique was devised to yield radiographic images that alleviate superimposition at the trifurcation of the maxillary first molar. Purpose: to observe and compare the radiographic images of the trifurcation region of the maxillary first molar generated through the SLOB technique with the film holder modification set at a mesial and distal angulation of 20Ëš with the parallel technique. Methods: This observational analytic research encompassed a sample size of 24 instances. Each individual sample underwent three separate exposures: the SLOB technique with a horizontal angulation of 20Ëš towards both mesial and distal directions, and the parallel technique (serving as the control). Results: a significant difference in radiographic images of the trifurcation region of the maxillary first molar obtained through the SLOB technique, employing the film holder modification with a mesial angulation of 20Ëš and a distal angulation of 20Ëš, as opposed to the parallel technique (control). Conclusion: A radiographic image capturing the trifurcation of the maxillary first molar, devoid of superimposition, was successfully generated through the SLOB technique incorporating a horizontal angulation of 20Ëš towards the distal direction.